Dynamics of Epileptic Activity in a Peculiar Case of Childhood Absence Epilepsy and Correlation with Thalamic Levels of GABA - Leal, A (2016)
Childhood absence epilepsy (CAE) is a syndrome with well-defined electroclinical features but unknown pathological basis. An increased thalamic tonic GABA inhibition has recently been discovered on animal models (Cope et al., 2009), but its relevance for human CAE is unproven. METHODS: We studied an 11-year-old boy, presenting the typical clinical features of CAE, but spike-wave discharges (SWD) restricted to one hemisphere. RESULTS: High-resolution EEG failed to demonstrate independent contralateral hemisphere epileptic activity. Consistently, simultaneous EEG-fMRI revealed the typical thalamic BOLD activation, associated with caudate and default mode network deactivation, but restricted to the hemisphere with SWD. Cortical BOLD activations were localized on the ipsilateral pars transverse. Magnetic resonance spectroscopy, using MEGA-PRESS, showed that the GABA/creatine ratio was 2.6 times higher in the hemisphere with SWD than in the unaffected one, reflecting a higher GABA concentration. Similar comparisons for the patient's occipital cortex and thalamus of a healthy volunteer yielded asymmetries below 25%. SIGNIFICANCE: In a clinical case of CAE with EEG and fMRI-BOLD manifestations restricted to one hemisphere, we found an associated increase in thalamic GABA concentration consistent with a role for this abnormality in human CAE.